PENGARUH PEMBERIAN EDUKASI LEAFLET TERHADAP PENGETAHUAN TENTANG HIPOTERMIA PADA PENDAKI GUNUNG DI GUNUNG ANDONG - Tanujiarso, Bagus Ananta; Pratama, Gusma Rizky; Sari, Rinda Intan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
At present, most people, within specific age, like hiking. However, not all hikers are aware of the danger of hypothermia. Hypothermia refers to heat loss in humans that practically lowers the temperature. From 2013 to 2015, 41 hikers died due to hypothermia. Many hypothermia cases and information are not relevant to health science. These problems worsen the preparation and management of hypothermia. One of the preventions is - providing hypothermia education so the mortality rates of hikers due to hypothermia could be prevented. This study aims to determine the effect of providing educational leaflets on knowledge about polythermia in mountaineers on Mount Andong. The type of research used is quantitative research with a pre-experimental design one group pre test-post test design. This research will be carried out at the Gunung Andong Via Sawit Basecamp in May 2023. The sampling technique used is the Accidental Sampling technique. The sample used in this study was 55 climbers. In this study, respondents were given the opportunity to read the leaflet for 10 minutes. The statistical test used in this study used the Wilcoxon test. The results showed the mean score before the treatment was 81.57 with an SD of 9.38, a minimum score of 47, and a maximum score of 100. On the other hand, the mean score after the intervention was 89.65 with an SD of 7.82, a minimum score of 76, and a maximum score of 100. The researchers concluded the cognitive score of hypothermia improved after the implementation of leaflet education media. The researcher expects these research results as the future reference of hypothermia dangers, health care services for hypothermia hiker victims, and literature works to improve the awareness of hypothermia dangers.